STRUKTUR EKONOMI POTENSIAL DAN DAYA SAING ANTAR SEKTOR DI KABUPATEN/KOTA DI KALIMANTAN SELATAN - M. Rusmin Nuryadin; Nasrudin Nasrudin; Dessy Maulina (Universitas Bina Taruna Gorontalo, 2023)
The aim of the study was to determine the potential economic structure and competitiveness between economic sectors in districts/cities in South Kalimantan. Shift Share analysis was used as the research method. The results of the study showed that during the period 2012-2018, the economy in districts/cities in South Kalimantan, totaling 13 districts/cities, had a competitive sector for each district/city, which could be seen from the positive Cij value. It indicated that a sector had competitiveness and specialization. In other words, having competitive advantage showed the capability of a region to market its products outside the region / abroad / global market. In 13 districts/cities in South Kalimantan, they were still quite controlled by the sectors of agriculture, forestry and fishery, mining and quarrying sectors, Processing industry; Procurement of electricity and gas, Procurement, Construction; Wholesale and retail trade, repairs, Transportation and warehousing, Provision of accommodation and food and drink, Real estate, Corporate services, Government administration of defense and social security, Educational services, Health services and social activities. However, in terms of negative or less competitive sectors, they were information and communication sector, financial services and other services.